Estimating water balance of Tegona watershed in southeastern Ethiopia, using SWAT model - Woldeyohannes, M. (Madda Walabu University, 2016)
Water resource development is certainly the basic and crucial infrastructure for a nation’s sustainable development. To utilize water resources in a sustainable manner, it is necessary to understand the quantity and quality in space and time. This study was initiated with the objective of evaluating the performance and applicability of the Soil and Water Assessment Tool (SWAT) in analyzing the influence of hydrologic parameters on the stream flow variability and estimation of monthly water yield at the outlet of Tegona river watershed in Bale mountainous area.. The total 468 km2 area of the watershed was subdivided into 12 sub-basins and 60 hydrologic response units (HRUs). Sensitivity analysis, model calibration and validation were made to evaluate the model performance for simulation of stream flow on monthly time step. The calibrated SWAT model performed well for simulation of monthly stream flow. Statistical model performance measures, coefficient of determination (r2) of 0.71, the Nash-Sutcliffe simulation efficiency (ENS) of 0.77 and Percent difference (D) of 8.33, for monthly calibration and 0.86, 0.83 and -12.25 respectively for validation, indicated good to very good performance of the model simulation. Mean monthly and annual water yield simulated with the calibrated model were found to be 23.7 mm and 284.2 mm, respectively. The model slightly overestimated the flow on most of rainy months. The baseflow separation result indicated that subsurface flow was source of water in the study watershed. Overall, the model demonstrated good performance in capturing the patterns and trend of the observed flow series, which confirmed the appropriateness of the model for future scenario simulation. Therefore, it is recommended that SWAT model can be a potential tool for simulation of stream flow and water balance components of ungauged watershed in the highlands of Ethiopia with similar hydro-meteorological characteristics to Tegona watershed.